Encapsulation of Mesenchymal Stem Cells Improves Vascularization of Alginate-Based Scaffolds. - Steiner, Dominik; Lingens, Lara; Fischer, Laura; Köhn, Katrin; Detsch, Rainer; Boccaccini, Aldo R.; Fey, Tobias; Greil, Peter; Weis, Christian; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas (Tissue Engineering: Parts A, B, and C, 2018)
DiI-labeled MSCs/mL ADA-GEL. Four weeks postoperatively, tissue formation and vascularization were investigated by histology and microcomputed tomography. We were able to prove vascularization originating from the AV loop in both groups with statistically significant more vessels in group B containing MSCs. Moreover, encapsulated MSCs promoted biodegradation of the ADA-GEL microcapsules. In the present study, we were able to demonstrate for the first time, the successful vascularization of ADA-GEL microcapsules by means of the AV loop. Furthermore, ADA-GEL displayed a good biocompatibility and encapsulation of MSCs into ADA-GEL microcapsule-enhanced vascularization as well as biodegradation.

Impact of Endothelial Progenitor Cells in the Vascularization of Osteogenic Scaffolds - Steiner, Dominik; Reinhardt, Lea; Fischer, Laura; Popp, Vanessa; Körner, Carolin; Geppert, Carol-Immanuel; Bäuerle, Tobias; Horch, Raymund E.; Arkudas, Andreas (Cells, 2022)
The microvascular endothelial network plays an important role in osteogenesis, bone regeneration and bone tissue engineering. Endothelial progenitor cells (EPCs) display a high angiogenic and vasculogenic potential. The endothelialization of scaffolds with endothelial progenitor cells supports vascularization and tissue formation. In addition, EPCs enhance the osteogenic differentiation and bone formation of mesenchymal stem cells (MSCs). This study aimed to investigate the impact of EPCs on vascularization and bone formation of a hydroxyapatite (HA) and beta-tricalcium phosphate (ß-TCP)–fibrin scaffold. Three groups were designed: a scaffold-only group (A), a scaffold and EPC group (B), and a scaffold and EPC/MSC group (C). The HA/ß–TCP–fibrin scaffolds were placed in a porous titanium chamber permitting extrinsic vascularization from the surrounding tissue. Additionally, intrinsic vascularization was achieved by means of an arteriovenous loop (AV loop). After 12 weeks, the specimens were explanted and investigated by histology and CT. We were able to prove a strong scaffold vascularization in all groups. No differences regarding the vessel number and density were detected between the groups. Moreover, we were able to prove bone formation in the coimplantation group. Taken together, the AV loop is a powerful tool for vascularization which is independent from scaffold cellularization with endothelial progenitor cells’ prior implantation.
CRIS-Team Scopus Importer:2022-03-18
Keywords: AV loop; Bone tissue engineering; Endothelial progenitor cell; Mesenchymal stem cell; Vascularization

Intrinsic Vascularization of Recombinant eADF4(C16) Spider Silk Matrices in the Arteriovenous Loop Model - Steiner, Dominik; Lang, Gregor; Fischer, Laura; Winkler, Sophie; Fey, Tobias; Greil, Peter; Scheibel, Thomas; Horch, Raymund E.; Arkudas, Andreas (Tissue Engineering: Parts A, B, and C, 2019)
The surgically induced angiogenesis by means of arteriovenous (AV) loops represents a powerful method to significantly enhance vascularization of biomaterials. Regarding tissue engineering applications, spider silk is a promising biomaterial with a good biocompatibility and slow biodegradation. This study aims at investigating vascularization as well as de novo tissue formation of fibrous matrices made of electro-spun (ES) or wet-spun (WS) engineered ADF4(C16) spider silks in the rat AV loop model. Either ES or WS spider silk fibrous matrices were filled into Teflon chambers. Intrinsic vascularization was induced by means of an AV loop. After 4 weeks of vascularization, de novo tissue formation and biocompatibility were analyzed. Regardless of their significantly differing fiber diameters, both ES and WS eADF4(C16) fiber matrices displayed a good biocompatibility and initiated de novo tissue formation as well as vessel formation. Both matrices demonstrated partial vascularization originating from the AV loop, with more vessels in spider silk matrices with lower fiber diameters. We were able to demonstrate intrinsic vascularization of spider silk fibrous matrices by means of the AV loop. Moreover, our study indicates that the adjustment of the fiber diameter of engineered spider silks enables new possibilities to optimize vascularization.
CRIS-Team WoS Importer:2019-05-17